The young Karl Marx : German philosophy, modern politics, and human flourishing - Leopold, David (Ideas in context, 2007)
The Young Karl Marx is an innovative and important study of Marx's early writings. These writings provide the fascinating spectacle of a powerful and imaginative intellect wrestling with complex and significant issues, but they also present formidable interpretative obstacles to modern readers. David Leopold shows how an understanding of their intellectual and cultural context can illuminate the political dimension of these works. An erudite yet accessible discussion of Marx's influences and targets frames the author's critical engagement with Marx's account of the emergence, character, and (future) replacement of the modern state. This combination of historical and analytical approaches results in a sympathetic, but not uncritical, exploration of such fundamental themes as alienation, citizenship, community, anti-semitism, and utopianism. The Young Karl Marx is a scholarly and original work which provides a radical and persuasive reinterpretation of Marx's complex and often misunderstood views of German philosophy, modern politics, and human flourishing.